2022
DOI: 10.3390/cancers14051171
|View full text |Cite
|
Sign up to set email alerts
|

The Use of miRNAs in Predicting Response to Neoadjuvant Therapy in Oesophageal Cancer

Abstract: Oesophageal cancer (OC) is the ninth most common cancer worldwide. Patients receive neoadjuvant therapy (NAT) as standard of care, but less than 20% of patients with oesophageal adenocarcinoma (OAC) or a third of oesophageal squamous cell carcinoma (OSCC) patients, obtain a clinically meaningful response. Developing a method of determining a patient’s response to NAT before treatment will allow rational treatment decisions to be made, thus improving patient outcome and quality of life. (1) Background: To deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 77 publications
(153 reference statements)
0
4
0
Order By: Relevance
“…38 Notably while some authors categorise T2N0 disease as early and amenable to endomucosal resection (EMR), NICE supports the use of NAT in this cohort, likely to minimise local recurrence risk from micro-metastases. 39,40 It can be readily appreciated that histology, TNM staging, and an assessment of patient fitness (commonly quantified by the WHO Performance Status classification) account for the bulk of decision critical parameters. While the concept of comorbidity is acknowledged, especially when determining suitability for palliative chemotherapy, such guidelines remain simplistic, rarely factoring in dimensions such as high-risk comorbidities, social variables, or even ease of patient access to CRT centres.…”
Section: Decision-making Within Ocmentioning
confidence: 99%
“…38 Notably while some authors categorise T2N0 disease as early and amenable to endomucosal resection (EMR), NICE supports the use of NAT in this cohort, likely to minimise local recurrence risk from micro-metastases. 39,40 It can be readily appreciated that histology, TNM staging, and an assessment of patient fitness (commonly quantified by the WHO Performance Status classification) account for the bulk of decision critical parameters. While the concept of comorbidity is acknowledged, especially when determining suitability for palliative chemotherapy, such guidelines remain simplistic, rarely factoring in dimensions such as high-risk comorbidities, social variables, or even ease of patient access to CRT centres.…”
Section: Decision-making Within Ocmentioning
confidence: 99%
“…MiRNA Let-7 is involved in epigenetic switches, which lead to prostate cancer cell transformation . In addition, miRNA-99b, miRNA-451, miRNA-505, and miRNA-193b are valuable biomarkers for neoadjuvant therapy in esophageal cancer . These examples indicate that accurate and sensitive detection of miRNAs is of great significance in the early treatment and diagnosis of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…11 In addition, miRNA-99b, miRNA-451, miRNA-505, and miRNA-193b are valuable biomarkers for neoadjuvant therapy in esophageal cancer. 12 These examples indicate that accurate and sensitive detection of miRNAs is of great significance in the early treatment and diagnosis of cancer. Several analytical methods have been used to monitor miRNAs, such as fluorescence, 13,14 colorimetry, 15 surface-enhanced Raman, 16 chemiluminescence, 17 and electrochemical methods.…”
Section: ■ Introductionmentioning
confidence: 99%
“…MicroRNAs are endogenously expressed short non-coding RNA molecules of 19–25 nucleotides in length that are involved in post-transcriptional gene regulation. Emerging evidence has revealed that microRNAs are involved in the development, progression, and clinical outcome of ESCC [ 6–8 ]. MicroRNAs are not only potential biomarkers for ESCC, but may also be useful in advanced RNA therapy for treating ESCC [ 9 ].…”
Section: Introductionmentioning
confidence: 99%